Prediction of Gaseous Attenuation of Satellite Signal in Nigeria - Moses Oluwamuyiwa Olla; Akinsanmi Olaitan; Oluwafemi Ilesanmi Banjo; Oluwole Sunday Ayodele (Newinera Publisher, 2022)
It would be noticed that the rate at which people are demanding for satellite services has drastically increased due to increment in population. However, one of the apprehensions of satellite telecommunication engineer is the effects imposed on the earth-to space path link by gaseous attenuation. The research conducted in this paper bordered about investigation with comparison of prediction models for gas attenuation in the six locations in Nigeria, with each of the location taken from six geopolitical within the country. The cities considered for the analysis are: Kaduna (), Lagos (), Abuja (), Portharcort (), Enugu () and Bauchi (). Five-year radiosonde data were used in predicting gas attenuation in the cities selected which represent the geographical characteristics of each zone. Monthly variation of tropospheric components for each zone were computed. Influence of gas attenuation at different frequency bands for each zone were analysed. The results indicated that at clear-sky scenario, gas attenuation effects are still seen on satellite communication. Therefore, this research work would provide the needed statistical data of gas attenuation which would be of tremendous advantage for the link designers for their subsequent planning and design of good telecommunication systems in the six geopolitical zones of Nigeria.